A TPE-PP composite material for folding joints in pet strollers and its preparation method
By using a multi-layer composite material structure and radiation cross-linking technology, the balance between high rigidity and high toughness of the folding joints of pet strollers has been solved, improving the fatigue resistance and environmental adaptability of the materials, extending their service life and providing antibacterial and anti-mildew functions.
Patent Information
- Application Number
- CN202511387568.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-26
- Publication Date
- 2025-12-02
- Estimated Expiration
- 2045-09-26
AI Technical Summary
Existing materials are difficult to simultaneously meet the requirements of high rigidity and high toughness in the folding joints of pet strollers, and they face environmental challenges such as UV aging, sudden temperature changes and microbial growth when used outdoors.
The material employs a multi-layer composite material structure, including a base layer, a functional layer, and a surface layer. It combines reinforced polypropylene-based composite materials, fatigue-resistant thermoplastic elastomers, and functionalized thermoplastic elastomers with radiation crosslinking technology to form an interpenetrating network structure, thereby improving the material's fatigue resistance and environmental adaptability.
It achieves high rigidity, high toughness, and multi-environmental resistance, significantly extending the service life of folding joints, reducing friction and wear, and providing antibacterial and anti-mildew functions, making it suitable for complex outdoor environments.
Smart Images

Figure CN120863177B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite materials technology, specifically to a TPE-PP composite material for folding joints of pet strollers and its preparation method. Background Technology
[0002] The folding joints of pet strollers are critical components that withstand repeated stresses from movement, and traditional materials struggle to simultaneously meet the requirements for rigidity and fatigue life. Existing folding joints are typically made of metal alloys or modified engineering plastics: while metal joints offer high strength, they are heavy, prone to corrosion, and susceptible to rust; engineering plastics such as nylon or ordinary polypropylene joints are lightweight and rust-free, but often lack sufficient fatigue resistance, easily cracking or experiencing strength degradation under prolonged repeated folding or low-temperature impacts. In particular, homopolymer polypropylene (PP), although possessing high rigidity and low density, is inherently brittle, and its impact strength drops sharply at low temperatures, making it unsuitable for withstanding the frequent impacts and vibrations of the folding components in pet strollers. To improve toughness, PP is typically modified by adding rubber or elastomers, such as blending ethylene propylene diene monomer (EPDM) or polyolefin elastomers (POE) to significantly enhance its low-temperature impact resistance. However, simply adding elastomers can lead to a decrease in material stiffness and strength, and may cause creep deformation under sustained high loads, failing to provide sufficient structural support. For example, prior art patent CN103289213A discloses an EPDM / PP / TPE ternary blend closed-cell foam material and its manufacturing process, wherein the material is formulated in the following weight ratio. The raw materials used to prepare the product are: 20-90 PHR of EPDM rubber, 8-25 PHR of polypropylene resin, 8-60 PHR of thermoplastic elastomer (TPE), 3-35 PHR of compatibilizer, 0.4-2 PHR of stearic acid, 1.5-5 PHR of zinc oxide, 0-4 PHR of softener, 0.3-1.5 PHR of antioxidant, 0.8-2.5 PHR of crosslinking agent, 0.3-2 PHR of co-crosslinking agent, and 1.5-10 PHR of foaming agent. The formulation improves the overall performance through the mixing and compounding of materials, but it cannot meet the requirements for use under long-term fatigue conditions.
[0003] On the other hand, the introduction of reinforcing fillers can significantly improve the stiffness and heat resistance of plastics such as PP. However, the interfacial bonding between glass fiber and the non-polar polypropylene matrix is weak. Without proper interfacial compatibility treatment, the interface is prone to degradation under cyclic stress and environmental effects, leading to a decrease in the fatigue life and damp heat resistance of the composite material. Simultaneously, directly adding high-content fiber fillers can make the material brittle and reduce impact toughness, requiring the addition of toughening agents to mitigate this. In traditional methods, it is often difficult to achieve a balance between adding elastomers and adding rigid fillers: elastomers improve toughness but reduce stiffness, while rigid fillers increase strength but weaken toughness. Therefore, it is difficult for a single material system to achieve a balance between high strength and high toughness. Furthermore, ordinary plastic materials face environmental challenges such as UV aging, sudden temperature changes, and microbial growth when used outdoors.
[0004] In summary, existing technologies lack a novel material solution specifically designed for the use of folding joints in pet strollers. To address these needs, this invention provides an innovative multilayer composite material structure and its preparation method, overcoming the performance trade-offs inherent in traditional materials. Summary of the Invention
[0005] The main objective of this invention is to provide a TPE-PP multilayer composite material for folding joints in pet strollers, overcoming the shortcomings of existing single-material systems in terms of fatigue resistance and environmental adaptability. By organically combining material layers with different functions and employing a special process to ensure a strong bond between the layers, the material of this invention can simultaneously achieve high rigidity, high toughness, and multiple environmental resistance properties, thereby significantly extending the service life of the folding joint and improving its reliability.
[0006] The specific technical solution is as follows:
[0007] A TPE-PP composite material for folding joints in pet strollers is composed of a multi-layer composite structure, including a base layer, a functional layer, and a surface layer. The base layer and the functional layer, as well as the functional layer and the surface layer, are tightly bonded to form an interpenetrating network structure. The base layer is made of reinforced polypropylene-based composite material, the functional layer is made of fatigue-resistant thermoplastic elastomer composite material, and the surface layer is made of functionalized thermoplastic elastomer material.
[0008] Further, the base layer, by weight, consists of 50-70% highly crystalline polypropylene, 20-35% glass fiber reinforced polar plastic, 5-10% polyolefin elastomer toughening agent, and 3-5% compatibilizer; the functional layer consists of 40-60% hydrogenated styrene-butadiene-styrene block copolymer, 20-30% polyolefin plasticizer, 15-25% nano-silica, and 2-5% antioxidant; the surface layer consists of 85-90% matrix elastomer, 5-8% polytetrafluoroethylene micropowder, 3-5% silver-loaded zinc zeolite antibacterial agent, and 2-3% UV stabilizer.
[0009] Furthermore, the glass fiber reinforced polar plastic is glass fiber reinforced nylon 6, with a glass fiber content of 40%; the compatibilizer is maleic anhydride-grafted polypropylene; the polyolefin plasticizer is white oil plasticizer; the antioxidant is a compound of antioxidant 168 and antioxidant 1010 in a 1:1 ratio; and the UV stabilizer is a mixture of hindered amine light stabilizer and UV absorber.
[0010] This invention also provides a method for preparing a TPE-PP composite material for a folding joint of a pet stroller, specifically including the following steps:
[0011] S1: The glass fiber reinforced polar plastic used in the base layer is dried in a vacuum oven at 120°C for 4 hours to remove adsorbed moisture; at the same time, the polyolefin elastomer toughening agent and compatibilizer are mixed evenly in a high-speed mixer; the nano SiO2 used in the functional layer and the polytetrafluoroethylene micro powder used in the surface layer are surface activated.
[0012] S2: Layered melt blending, the formulation raw materials of the base layer, functional layer and surface layer are respectively fed into three parallel screw extruders for melt blending and granulation, and the granules obtained are dried separately;
[0013] S3: The prepared base layer, functional layer and surface layer granules are placed in the feeding hoppers of three extruders respectively, and the three-layer composite billet is produced by three-machine co-extrusion; the three melt streams converge through the three-layer co-extrusion die head, and the molten three-layer billet immediately enters the online irradiation crosslinking device after leaving the die head. The irradiation process is carried out in a nitrogen protection environment.
[0014] S4: The irradiated three-layer composite preform immediately enters the cooling and shaping section. First, it passes through a 2-meter-long stainless steel cooling water tank, with the water temperature controlled at 30℃. Then, it is continuously transported by two pairs of traction rollers at a uniform speed. Finally, it is cut into pellets by a pelletizer to obtain the three-layer co-extruded TPE-PP composite material.
[0015] Furthermore, the surface activation described in S1 specifically includes: the nano-SiO2 used in the functional layer is surface-treated with KH-550 silane coupling agent at an amount of 2wt% relative to SiO2; the polytetrafluoroethylene micropowder used in the surface layer is treated with oxygen as the working gas in a plasma treatment device for 5 minutes to improve its surface energy.
[0016] Furthermore, the specific parameter settings for the layered melt blending described in S2 include: the base layer is extruded using a twin-screw extruder with a length-to-diameter ratio of 40:1, the temperature is gradually increased from 170-190°C in the feeding section to 195-215°C in the die head, and the screw speed is 300 rpm; the functional layer is extruded using a twin-screw extruder with the temperature increasing from 160-180°C in the feeding section to 180-200°C in the die head, and the screw speed is 250 rpm; the surface layer is extruded using a single-screw extruder with a temperature set at 150-185°C and a screw speed of 50 rpm.
[0017] Furthermore, the barrel temperatures of the three extruders described in S3 are set as follows: base layer 190-210℃, functional layer 180-200℃, and surface layer 170-190℃.
[0018] Furthermore, the three melt streams described in S3 converge through a three-layer co-extrusion die head, the die head having three sets of flow channels: the central flow channel supplies the base layer melt, the second annular flow channel supplies the functional layer melt, and the outermost annular flow channel supplies the surface layer melt; the thickness ratio of base layer: functional layer: surface layer = 2.0mm:1.0mm:0.1mm can also be controlled by adjusting the flow rate of the three melt streams and the die head gap width.
[0019] Furthermore, the parameters of the online irradiation crosslinking device described in S3 include: setting the electron energy to 5 MeV and the dose to 10 kGy.
[0020] The present invention also provides an application of TPE-PP composite material for folding joints of pet strollers. The folding joint components are processed by injection molding or compression molding of the granules of the composite material and applied to the joint structure of pet strollers that requires both high rigidity and high fatigue resistance.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) This invention achieves an effective combination of high strength and high toughness through the structural combination of a "rigid layer + elastic layer". The glass fiber reinforced PP in the base layer gives the material high initial stiffness and load-bearing capacity, while the elastomers in the functional layer and surface layer provide stress buffering and adaptive deformation capabilities. When the joint is repeatedly subjected to force during folding, the functional layer bears most of the cyclic strain, reducing the direct stress transmission to the rigid base layer, thereby delaying or even avoiding fatigue cracks in the base layer. In addition, the synergistic effect of toughening components such as nano-SiO2 and POE further inhibits crack initiation and propagation.
[0023] (2) This invention is designed with UV resistance, heat and humidity resistance, and antibacterial and anti-mildew properties for outdoor use. The material of this invention can adapt to long-term exposure to sun and rain, as well as damp and dirty outdoor environments, maintaining the stability and cleanliness of the joint structure.
[0024] (3) The self-lubricating effect of PTFE micropowder in the surface layer of this invention significantly reduces friction and wear during joint movement. The self-lubricating properties effectively improve the smoothness of joint movement, avoid the trouble of regularly adding lubricating oil to traditional joints, and help reduce wear dust generation, thus extending the service life of the joint. In addition, the addition of PTFE and the effect of radiation crosslinking also improve the dimensional stability and temperature resistance of the material.
[0025] (4) The material provided by this invention can be made into standard thermoplastic granules, which can be directly used for injection molding, extrusion and other processes to form pet stroller joint parts. The material has good fluidity and high thermal stability during processing, and the introduction of irradiation crosslinking process does not affect its processability. Attached Figure Description
[0026] Figure 1 This is a flowchart illustrating the preparation process of a TPE-PP composite material for a folding joint in a pet stroller according to the present invention.
[0027] Figure 2 This is a cross-sectional topography image obtained using a scanning electron microscope (SEM) in Experiment Example 1 of this invention.
[0028] Figure 3 This is a comparison chart of experimental results data for Experiment Example 2 of the present invention. Detailed Implementation
[0029] The following embodiments further explain and illustrate the technical solutions of the present invention. It should be specifically noted that each specific embodiment is a concretization and explanation of the technical solution and should not be considered as a limitation on the scope of protection of the present invention. Those skilled in the art still have the right to modify the technical solutions of these embodiments and make equivalent substitutions for some or all of the technical features, and these modifications or substitutions do not change the essence of the corresponding technical solutions, nor do they cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions described in the present invention.
[0030] This invention proposes a TPE-PP composite material for folding joints in pet strollers and its preparation method, as shown in the appendix. Figure 1 The diagram shown is a flowchart of the composite material preparation method of the present invention. The specific key technical solutions are designed as follows:
[0031] The composite material of this invention adopts a multi-layer structure design, including a base layer, a functional layer, and a surface layer stacked sequentially. The composition and function of each layer are as follows:
[0032] 1. Base Layer: A modified polypropylene-based reinforced composite material is used to provide the main rigidity and strength support required for the joint structure. Its formulation includes 50-70% highly crystalline polypropylene (PPH-5060) as the matrix resin, compounded with 20-35% glass fiber reinforced polar plastic to improve strength and modulus (the glass fiber (GF) content of this plastic is 40%), and 5-10% polyolefin elastomer (POE) as a toughening agent to improve impact toughness. Additionally, 3-5% maleic anhydride-grafted modified PP (PP-g-MAH) is added as a compatibilizer to enhance the compatibility of the components. Through this formulation design, the base layer forms a composite structure with both a rigid skeleton and a toughening dispersed phase: the glass fiber provides a high-modulus skeleton, while the POE elastomer particles dispersed in the PP matrix can induce plastic deformation in the matrix under impact loads to absorb energy, passivate, and inhibit crack propagation; the addition of the compatibilizer ensures good interfacial adhesion between PP and POE, as well as the glass fiber surface, achieving effective stress transfer between the rigid and flexible components. Preferably, the glass fiber is pretreated with a silane coupling agent, which can form an organic functional layer on the fiber surface, and chemically bond or hydrogen bond with the PP matrix to improve the interfacial shear strength. This not only prevents the fiber from agglomerating during the molding of the composite material, but also gives the composite material a more stable interface in a humid and hot environment, avoiding the decrease in interfacial strength caused by hydrolysis, etc.
[0033] 2. Functional Layer: Employing fatigue-resistant thermoplastic elastomer (TPE) based composite materials, this layer provides stress buffering and crack damping functions to the joint during repeated folding. The functional layer formulation includes 40–60% hydrogenated styrene-butadiene-styrene block copolymer (SEBS) as a continuous matrix, 20–30% polyolefin plasticizer to adjust hardness and glass transition temperature, 15–25% nano-silica (SiO2) particles as reinforcing filler, and 2–5% antioxidant to prevent thermo-oxidative aging during long-term use. SEBS is a soft elastomer with excellent elastic recovery and weather resistance. It can be repeatedly deformed under cyclic loading without permanent deformation or fatigue fracture. Nano-SiO2 particles have small size and high specific surface area. After surface organic modification, they can be well dispersed in the SEBS matrix, forming a large number of micro-stress concentration points. When the material is under stress, it induces micro-yielding in the matrix to dissipate energy and pins the crack tip to prevent its further propagation. In addition, the synergy of different toughening phases also helps to improve the fatigue resistance of the material. When the elastomer SEBS and POE coexist, they can form an "island" structure, which together absorbs the energy of microcracks generated by external forces and prevents crack fusion. The functional layer material is co-extruded with the base layer to achieve a certain degree of mutual penetration and entanglement at the interface between the two layers. This buffers the stress gradient between the base layer and the external load, preventing direct stress transmission that could lead to local fatigue in the base layer. In addition, the soft polymer chains of the functional layer can also provide a "passivation" effect on microcracks that may occur in the base layer. That is, when a fine crack appears in the base layer, the flexible network of the functional layer can prevent the crack from opening and disperse the stress, making it difficult for the crack to develop into macroscopic damage.
[0034] 3. Surface Layer: A modified functionalized TPE material is used, primarily providing self-lubrication, antibacterial, and anti-aging functions, while also maintaining a certain degree of toughness to accommodate deformation. The surface layer thickness is controlled at 0.1–0.2 mm. Its composition includes a matrix thermoplastic elastomer, preferably 85–90% SEBS compatible with the functional layer, and the addition of 5–8% polytetrafluoroethylene (PTFE) ultrafine powder, 3–5% inorganic antibacterial agent silver-zinc ion-loaded zeolite, and 2–3% UV stabilizer. PTFE micropowder has an extremely low coefficient of friction and self-lubricating properties. After being uniformly dispersed in the surface layer, it can form a friction-reducing and wear-resistant solid lubricant network on the moving surface of the folding joint. The PTFE micropowder in the surface layer of this invention allows the folding joint to move smoothly even under oil-free lubrication conditions, reducing wear and operating noise, while also preventing dust adhesion. The antibacterial agent is silver-zinc zeolite, which is a type of zeolite molecular sieve with silver ions (Ag) loaded onto it. + ) and zinc ions (Zn 2+ This inorganic antibacterial additive slowly releases Ag when the environment is humid. + and Zn 2+Both have broad-spectrum inhibitory and bactericidal effects on bacteria and fungi. Silver ions can disrupt the protein and DNA synthesis of microorganisms, while zinc ions have an inhibitory effect on mold. The two work together to give the material surface a long-lasting antibacterial and anti-mold capability, which is especially important for the long-term use of pet strollers in outdoor or humid environments. It can prevent mold growth on joint parts and ensure the hygiene and safety of pets and people. In terms of UV stabilizers, it is preferable to add light stabilizers such as hindered amine light stabilizers (HALS) and UV absorbers. A small amount of HALS can intercept free radicals generated during polymer photodegradation, thereby protecting the main chain of the material from further damage. UV absorbers such as benzophenone can absorb harmful UV bands in sunlight. By adding UV stabilizers, the surface layer can effectively improve the color and mechanical property stability of the composite material under sunlight exposure and prevent cracking and powdering caused by photo-oxidative aging.
[0035] 4. Interlayer Bonding and Structural Characteristics: The three-layer structure of this invention is prepared through a simultaneous co-extrusion process, allowing the base layer, functional layer, and surface layer in a molten state to be formed and tightly bonded in one step. During the co-extrusion process, due to the effects of temperature and pressure, a certain degree of polymer chain diffusion and entanglement occurs between the layers, forming physically interlocked interfaces. In addition, this invention introduces electron beam radiation crosslinking as a post-processing method. Immediately after the three-layer composite material is extruded, it is subjected to online irradiation. The high-energy electron beam can penetrate the entire thickness of the composite material, initiating free radical reactions in the polymer, causing crosslinking of polymer chains within each layer and at the interfaces. Radiation crosslinking not only improves the mechanical strength of the material, especially at high temperatures, but also activates the interface between the filler and the polymer matrix, improving interfacial adhesion. In this invention, irradiation causes chemical bonding bridging of the polymer chains at the interfaces between the base layer and the functional layer, and between the functional layer and the surface layer, further consolidating the interlayer bonding force. In fact, after electron beam irradiation, the multilayer structure exhibits characteristics similar to an interpenetrating network: there are no obvious boundaries at the interfaces, and the materials of each layer are interwoven at the molecular level, preventing delamination and damage under stress. This design avoids the interface delamination problem that may occur in traditional sandwich structures, and greatly improves the reliability of the material in resisting cyclic loads and environmental erosion.
[0036] Example 1
[0037] A method for preparing a TPE-PP composite material for a folding joint of a pet stroller is as follows:
[0038] Table 1. Detailed Information on Main Raw Materials:
[0039]
[0040] Base layer formulation: 60% PPH-5060 polypropylene, 28% glass fiber reinforced nylon 6 (GF content 40%), 8% POE elastomer, and 4% PP-g-MAH compatibilizer;
[0041] Functional layer formulation: SEBS elastomer 50%, white oil plasticizer 26%, nano SiO2 21%, antioxidant 1010 / 168 3%;
[0042] Surface layer formulation: 88% SEBS elastomer, 6% PTFE micro powder, 4% silver-loaded zinc ion zeolite, and 2% UV absorber (HALS+UV absorber).
[0043] S1: The glass fiber reinforced nylon granules used in the base layer are dried in a vacuum oven at 120℃ for 4 hours to remove adsorbed moisture; at the same time, the POE elastomer and compatibilizer are mixed evenly in a high-speed mixer; the nano-SiO2 used in the functional layer is surface-treated with KH-550 silane coupling agent before addition, with an amount of 2wt% relative to SiO2, specifically by suspending SiO2 in an ethanol solution, adding the coupling agent, stirring for 1 hour, and then drying; the PTFE micro powder used in the surface layer is treated with oxygen as the working gas in a plasma treatment device for 5 minutes to improve its surface energy; the silver-zinc antibacterial agent and anti-UV additive are ready for use directly, and all raw materials are weighed according to the formula.
[0044] S2: Layered melt blending. The raw materials for the base layer, functional layer, and surface layer are fed into three parallel screw extruders for melt blending and granulation. The specific process parameters are as follows:
[0045] The base layer twin-screw extruder has a length-to-diameter ratio of 40:1. The temperature setting gradually increases from 180℃ in the feeding section to 205℃ in the die head. The screw speed is 300rpm. Vacuum exhaust is used to remove volatiles. The extruded material is granulated by water cooling and forming into composite pellets to obtain the base layer.
[0046] Functional layer twin-screw extruder: The temperature increases from 170°C in the feeding section to 190°C in the die head, the screw speed is 250 rpm, and vacuum exhaust is also set. SEBS elastomer begins to melt in the first mixing zone, white oil plasticizer is pumped in the second zone and mixed with molten SEBS to form an oil-filled melt. Nano SiO2 and antioxidant are added in the third mixing zone. The die head is water-cooled and pelletized to obtain functional layer elastomer granules.
[0047] Surface layer single-screw extruder: Temperature set at 160-175℃, screw speed at 50 rpm. SEBS matrix elastomer and various additives are added to the hopper for melting and plasticization. Since PTFE is a high-melting-point polymer, it does not melt within this temperature range but is mixed into the melt in the form of solid particles. In order to ensure uniform mixing, a perforated plate resistance element is used to increase melt shear. The extruded melt is directly pressed against a water-cooled roller for cooling and then pelletized to obtain surface layer functional granules. The above-mentioned granules are dried separately and then used for later use.
[0048] S3: The prepared base layer, functional layer, and surface layer granules are placed in the feeding hoppers of three extruders, and a three-layer composite billet is produced by co-extrusion. The barrel temperatures of the three extruders are set as follows: base layer 200℃, functional layer 190℃, and surface layer 180℃. The three melt streams converge through a specially designed three-layer co-extrusion die: the die has three sets of flow channels inside, the central flow channel for the base layer melt, the second annular flow channel for the functional layer melt, and the outermost annular flow channel for the surface layer melt. By adjusting the flow rate of each extruder and the die gap width, the thickness ratio of each layer is controlled to be base layer: functional layer: surface layer = 2.0mm: 1.0mm: 0.1mm. This thickness and ratio is the layer thickness at the time of die exit. After leaving the die, the molten three-layer billet immediately enters the online irradiation crosslinking device. In this embodiment, the parameters of electron energy 5MeV and dose 10kGy are selected to irradiate the molten billet. The irradiation process is carried out in a nitrogen-protected environment.
[0049] S4: The irradiated three-layer composite material immediately enters the cooling and shaping section. First, it passes through a 2-meter-long stainless steel cooling water tank with the water temperature controlled at 30℃ to quickly cool and solidify the sheet. Then, the solidified composite material is continuously conveyed by two pairs of traction rollers at a uniform speed, and the edges are trimmed by an online edge trimmer to remove excess. Finally, it is cut into granules with a width of 3mm and a length of 4mm by a pelletizer to obtain three-layer co-extruded composite material granules, which can be directly used for injection molding.
[0050] Example 2
[0051] The preparation method is the same as in Example 1, except that:
[0052] Base layer formulation: 50% PPH-5060 polypropylene, 35% glass fiber reinforced nylon 6 (GF content 40%), 10% POE elastomer, and 5% PP-g-MAH compatibilizer;
[0053] Functional layer formulation: SEBS elastomer 40%, white oil plasticizer 30%, nano SiO2 25%, antioxidant 1010 / 168 5%;
[0054] Surface layer formulation: 85% SEBS elastomer, 7% PTFE micro powder, 5% silver-loaded zinc ion zeolite, and 3% UV absorber (HALS+UV absorber).
[0055] In S2, the temperature setting of the base layer twin-screw extruder gradually increases from 190°C in the feeding section to 215°C in the die head; the temperature of the functional layer twin-screw extruder increases from 180°C in the feeding section to 200°C in the die head; and the temperature setting of the surface layer single-screw extruder is 170-185°C.
[0056] The barrel temperatures of the three extruders in S3 are set as follows: base layer 210℃, functional layer 200℃, and surface layer 190℃.
[0057] All other steps are the same.
[0058] Example 3
[0059] The preparation method is the same as in Example 1, except that:
[0060] Base layer formulation: 70% PPH-5060 polypropylene, 22% glass fiber reinforced nylon 6 (GF content 40%), 5% POE elastomer, 3% PP-g-MAH compatibilizer;
[0061] Functional layer formulation: SEBS elastomer 60%, white oil plasticizer 23%, nano SiO2 15%, antioxidant 1010 / 168 2%;
[0062] Surface layer formulation: 90% SEBS elastomer, 5% PTFE micro powder, 3% silver-loaded zinc ion zeolite, and 2% UV absorber (HALS+UV absorber).
[0063] In S2, the temperature setting of the base layer twin-screw extruder gradually increases from 170°C in the feeding section to 195°C in the die head; the temperature of the functional layer twin-screw extruder increases from 160°C in the feeding section to 180°C in the die head; and the temperature setting of the surface layer single-screw extruder is 150-165°C.
[0064] The barrel temperatures of the three extruders in S3 are set as follows: 190°C for the base layer, 180°C for the functional layer, and 170°C for the surface layer.
[0065] All other steps are the same.
[0066] Comparative Example 1
[0067] A commonly used 30% glass fiber reinforced PP material was selected as a comparative sample. Its composition is: 65% PP resin, 30% glass fiber, 5% compatibilizer, and it does not contain elastomers or functional additives. This material is equivalent to having only the basic layer function of this invention but without functional and surface layer designs.
[0068] Comparative Example 2
[0069] A high-toughness PP material was selected as a comparative sample to simulate a solution that only toughens without reinforcing. The composition is: 70% PP copolymer, 20% EPDM rubber, and 10% talc filler. The aforementioned components include basic antioxidants but no special functional agents. This material is equivalent to a high-toughness monolayer composite.
[0070] Comparative Example 3
[0071] Refer to the formulation and preparation method of Example 1, but omit the irradiation process in S3 and use the commonly used dynamic vulcanization extrusion process for crosslinking. Paraffin (Tianjin Lianlong New Material Co., Ltd.) and JR-1 crosslinking agent (Kingfa Science & Technology Co., Ltd.) are added before extrusion. All other steps are the same.
[0072] Experimental Example 1
[0073] The three-layer co-extruded composite material granules finally prepared in Example 1 were tested by scanning electron microscopy (SEM) under the following specific test conditions:
[0074] Sample preparation: Immerse the particulate sample in a Dewar flask filled with liquid nitrogen for at least 15 minutes to make the sample completely brittle. Use a pre-cooled clamp to pick up a brittle sample and quickly place it on a hard table. Apply a sharp impact force with a pre-cooled hammer or pliers to break it along the cross-section perpendicular to the extrusion flow direction. Select a sample fragment with a flat cross-section that allows simultaneous observation of the three-layer structure. Since the sample is non-conductive, it needs to be sputtered with gold to eliminate the charge accumulation effect during SEM observation. Use an ion sputtering instrument to sputter the cross-section with gold-palladium alloy as the target material. Set the sputtering current to 20-30 mA and the sputtering time to 60-90 seconds.
[0075] With the cross-section of the gold-sprayed sample facing upwards, firmly attach it to the metal sample stage of the SEM using conductive tape to ensure good electrical contact. The SEM equipment parameter settings are shown in Table 2.
[0076] Table 2. SEM Test Parameter Settings for Experiment Example 1:
[0077]
[0078] Test results attached (image) Figure 2As shown in the SEM images, the base layer (bottom region) exhibits an uneven fracture surface, composed of a polypropylene / polyamide 6 matrix reinforced with glass fiber and polyolefin elastomer rubber. The randomly distributed glass fiber ends appear as bright circular areas, with some fibers embedded within them, while others, pulled out, leave darker voids. The substrate polymer matrix itself exhibits a certain degree of roughness due to the semi-crystalline polypropylene / polyamide 6 blend. No clear boundary line is visible at the top of the base layer. Some features of the functional layer penetrate downwards, demonstrating the effect of irradiation crosslinking. The functional layer (middle region) appears relatively smooth, dispersed with numerous nano-silica particles, forming a fine, pepper-like contrast on the functional layer, with a fairly uniform dispersion. After irradiation, the functional layer bonds firmly to adjacent layers, with no clear boundary at the junction with the base layer or surface layer. The transition from the functional layer to the base layer and surface layer is gradual; even some silica spots can be observed in the base layer and surface layer regions outside the nominal interface, indicating interpenetration of the material. The thin surface layer (top region) contains polytetrafluoroethylene (PTFE) micropowder and silver / zinc ion zeolite additives. Microscopic images show micron-sized PTFE particles appearing as irregular white spots; these particles are solid during extrusion and exist as discrete inclusions. The silver / zinc zeolite appears as smaller bright spots, sparsely distributed due to the limited amount added. The surface layer exhibits a relatively smooth fracture texture with slight ductile tearing; despite its thin initial thickness, its presence is clearly visible in the top region of the image. The interface with the functional layer is continuous, without obvious lines or gaps; the polymers of the surface and functional layers undergo co-crosslinking, forming a gradual transition.
[0079] Experimental Example 2
[0080] The granules finally prepared in Examples 1-3 and Comparative Examples 1-3 were used to prepare standard test specimens and simulated pet car folding joint parts using an injection molding machine. The injection molding machine barrel temperature was 210°C and the mold temperature was 50°C. The molded joint samples had a smooth surface and no delamination. Mechanical and durability properties of the samples were tested, and the specific test settings are as follows:
[0081] (1) Tensile strength test: Use injection-molded 1A type standard dumbbell-shaped specimens, ensuring that the base layer faces outward when sampling, to simulate the actual stress of the joint; use a universal testing machine, set the clamping distance to 115mm, the testing speed to 50mm / min, the ambient temperature to 23±2℃, and require the specimen to be placed in the testing environment for no less than 24 hours; record the maximum tensile stress (MPa), and test at least 5 valid specimens for each group, and the results are expressed as mean ± standard deviation.
[0082] (2) Notched impact strength test: A standard injection-molded impact specimen (80.0×10.0×4.0mm) was used, and a V-notch with a depth of 2.5mm was machined on a special sample preparation machine; the test was conducted using a cantilever beam impact testing machine, with the pendulum energy set to 5.5J and the test temperature set to -20℃. The specimen was placed in an alcohol bath for at least 2 hours to ensure that the center temperature of the specimen reached -20℃, and the test was completed within 15 seconds after removal; the impact absorbed energy was recorded, and the impact strength per unit notch length (kJ / m) was calculated. 2 Each group should test at least 5 splines, and the results are expressed as mean ± standard deviation.
[0083] (3) Three-point bending fatigue test: simulate the durability of the joint under repeated bending load. The specimen is an actual injection-molded pet car joint hinge component. The test is conducted using a high-frequency servo hydraulic fatigue testing machine with a three-point bending fixture. The span is fixed according to the size of the specimen. The load mode is force control, sine wave, load range ±50N, frequency 5Hz, and the number of cycles is hundreds of thousands. The specimen is completely broken or terminated when the set number of cycles is reached. The number of specimens in each group that have not been damaged after 100,000 cycles is recorded.
[0084] (4) Friction and wear test: simulate the rotating friction pair between the joint and the steel pin. The upper sample is a standard friction pin (Ø4×10mm) made of the joint hinge material. The lower sample is a standard GCr15 pin with a hardness of HRC60 and a surface roughness Ra≤0.2μm. The pin-disc wear tester is used for testing. The load is set to 10N, the sliding speed is 0.1m / s, the rotation radius is set according to the fixture, and the total sliding distance is equivalent to the distance of 1000 rotations. The environment is set to room temperature and dry state. After the test, the mass loss of the friction pin is weighed with a precision electronic balance, which is the wear amount (mg). Three parallel samples are tested in each group.
[0085] (5) Ultraviolet accelerated aging test: The QUV accelerated aging test chamber was used for testing, equipped with UVA-340 lamps; the light irradiation cycle was set to 8 hours of ultraviolet irradiation, the blackboard temperature was 60℃, the condensation cycle was 4 hours of condensation, the blackboard temperature was 50℃, and the total time was 500 hours; after the test, the aged sample was taken and tested according to the tensile strength test standard, the percentage of its strength relative to the unaged sample was calculated, and the color change, powdering, cracking, wrinkling and other phenomena were visually observed and recorded.
[0086] (6) Damp heat aging test: The constant temperature and humidity chamber was used for the test. The temperature was set at 50±2℃, the relative humidity was 90±5%RH, and the time was set to 2 weeks (336 hours). After the test, the surface mold growth was observed visually and under a microscope and rated from 0 to 5. Grade 0 means no mold spots and Grade 5 means severe mold spots.
[0087] The specific test results are shown in Table 3 and Appendix. Figure 3 As shown.
[0088] Table 3 Comparison of test results for Experiment Example 2:
[0089]
[0090] The results from the charts show that the high-rigidity PP+GF structure in Comparative Example 1 exhibits high tensile strength but low impact strength, making it brittle and prone to fracture under low temperatures or impact loads. The high-toughness PP structure in Comparative Example 2 exhibits high impact strength but excessively low tensile strength, making it susceptible to plastic deformation and insufficient stiffness as a structural component. The embodiments achieve a good balance between strength and toughness through a composite structure of a rigid base layer and a toughening functional layer. In fatigue performance testing, all embodiments passed 100,000 fatigue cycles. This is attributed to the excellent fatigue resistance of the POE / SEBS elastomer and the stable network structure formed by radiation crosslinking, which effectively inhibits crack initiation and propagation. Comparative Example 1 exhibits the worst fatigue performance due to its high brittleness. While Comparative Examples 2 and 3 possess some toughness, the former lacks sufficient strength, and the latter, due to the lack of radiation crosslinking, suffers from low interlayer bonding and material cohesive energy, making them more prone to damage and failure under repeated stress. In the wear resistance test, the wear amount of the Example was significantly lower than that of all comparative examples. This was mainly due to the PTFE micropowder in the surface layer, which effectively reduced the coefficient of friction and wear rate as a solid lubricant. Although Comparative Example 1 was hard, it caused significant wear on the steel shaft and also suffered severe wear itself. The wear amounts of Comparative Examples 2 and 3 were moderate. In the UV accelerated aging test, the Example maintained a high strength retention rate, thanks to the synergistic effect of HALS and UV-326 in the surface layer, which effectively quenched free radicals and absorbed ultraviolet light, protecting the matrix resin. Comparative Examples 1 and 2 lacked sufficient UV protection and suffered severe degradation. Although Comparative Example 3 contained UV stabilizers in its formulation, the lack of irradiation crosslinking led to agent migration or a decrease in the material's weather resistance, resulting in a lower performance retention rate than the Example. In the damp heat aging test, Example 1 showed excellent anti-mildew performance due to the presence of silver-zinc ion-loaded zeolite antibacterial agent in the surface layer; Comparative Example 3 had antibacterial agent but its dispersibility or effectiveness was slightly worse; Comparative Examples 1 and 2 had no antibacterial design at all, and mold grew in large quantities; Comparative Example 2, due to the presence of EPDM and talc, was more prone to moisture absorption and mold growth, and received the worst rating.
[0091] In summary, the three-layer composite material provided by this invention, through reasonable layered design, optimized formulation, and key irradiation crosslinking process, successfully prepared a pet stroller joint material with excellent comprehensive performance. It is significantly superior to existing single materials or non-irradiated process materials in terms of high strength, high toughness, fatigue resistance, wear resistance, UV aging resistance, and antibacterial and antifungal properties, thus meeting the complex requirements of this application scenario.
Claims
1. A TPE-PP composite material for folding joints of pet strollers, comprising a multi-layered composite structure, including: The invention comprises a base layer, a functional layer, and a surface layer, characterized in that: the base layer and the functional layer, and the functional layer and the surface layer are tightly bonded to form an interpenetrating network structure; the base layer is made of reinforced polypropylene-based composite material; the functional layer is made of fatigue-resistant thermoplastic elastomer composite material; and the surface layer is made of functionalized thermoplastic elastomer material. The base layer, by weight, consists of 50–70% highly crystalline polypropylene, 20–35% glass fiber reinforced polar plastic, 5–10% polyolefin elastomer toughening agent, and 3–5% compatibilizer. The functional layer consists of 40–60% hydrogenated styrene-butadiene-styrene block copolymer, 20–30% polyolefin plasticizer, 15–25% nano-silica, and 2–5% antioxidant. The surface layer consists of 85–90% matrix elastomer, 5–8% polytetrafluoroethylene micropowder, 3–5% silver-loaded zinc zeolite antibacterial agent, and 2–3% UV stabilizer.
2. The TPE-PP composite material for a folding joint of a pet stroller as described in claim 1, characterized in that, The glass fiber reinforced polar plastic is glass fiber reinforced nylon 6, with a glass fiber content of 40%; the compatibilizer is maleic anhydride grafted polypropylene; the polyolefin plasticizer is white oil plasticizer; the antioxidant is a compound of antioxidant 168 and antioxidant 1010 in a 1:1 ratio; and the UV stabilizer is a mixture of hindered amine light stabilizer and UV absorber.
3. A method for preparing a TPE-PP composite material for a folding joint of a pet stroller according to any one of claims 1-2, characterized in that, Specifically, the following steps are included: S1: The glass fiber reinforced polar plastic used in the base layer is dried in a vacuum oven at 120°C for 4 hours to remove adsorbed moisture; at the same time, the polyolefin elastomer toughening agent and compatibilizer are mixed evenly in a high-speed mixer; the nano SiO2 used in the functional layer and the polytetrafluoroethylene micro powder used in the surface layer are surface activated. S2: Layered melt blending, the formulation raw materials of the base layer, functional layer and surface layer are respectively fed into three parallel screw extruders for melt blending and granulation, and the granules obtained are dried separately; S3: The prepared base layer, functional layer and surface layer granules are placed in the feeding hoppers of three extruders respectively, and the three-layer composite billet is produced by three-machine co-extrusion; the three melt streams converge through the three-layer co-extrusion die head, and the molten three-layer billet immediately enters the online irradiation crosslinking device after leaving the die head. The irradiation process is carried out in a nitrogen protection environment. S4: The irradiated three-layer composite preform immediately enters the cooling and shaping section. First, it passes through a 2-meter-long stainless steel cooling water tank, with the water temperature controlled at 30℃. Then, it is continuously transported by two pairs of traction rollers at a uniform speed. Finally, it is cut into pellets by a pelletizer to obtain the three-layer co-extruded TPE-PP composite material.
4. The method for preparing a TPE-PP composite material for a folding joint of a pet stroller as described in claim 3, characterized in that, The surface activation described in S1 specifically includes: the nano-SiO2 used in the functional layer is surface-treated with KH-550 silane coupling agent at a dosage of 2wt% relative to SiO2; the polytetrafluoroethylene micropowder used in the surface layer is treated with oxygen as the working gas in a plasma treatment device for 5 minutes to improve its surface energy.
5. The method for preparing a TPE-PP composite material for a folding joint of a pet stroller as described in claim 3, characterized in that, The specific parameter settings for the layered melt blending described in S2 include: the base layer is extruded using a twin-screw extruder with a length-to-diameter ratio of 40:1, and the temperature is gradually increased from 170-190℃ in the feeding section to 195-215℃ in the die head, with a screw speed of 300 rpm; the functional layer is extruded using a twin-screw extruder with the temperature increasing from 160-180℃ in the feeding section to 180-200℃ in the die head, and a screw speed of 250 rpm; the surface layer is extruded using a single-screw extruder with a temperature set at 150-185℃ and a screw speed of 50 rpm.
6. The method for preparing a TPE-PP composite material for a folding joint of a pet stroller as described in claim 3, characterized in that, The three extruders described in S3 have the following barrel temperatures: base layer 190-210℃, functional layer 180-200℃, and surface layer 170-190℃.
7. The method for preparing a TPE-PP composite material for a folding joint of a pet stroller as described in claim 3, characterized in that, The three melt streams described in S3 converge through a three-layer co-extrusion die head. The die head has three sets of flow channels: the central flow channel supplies the base layer melt, the second annular flow channel supplies the functional layer melt, and the outermost annular flow channel supplies the surface layer melt. The thickness ratio of base layer: functional layer: surface layer = 2.0mm:1.0mm:0.1mm can be controlled by adjusting the flow rate of the three melt streams and the die head gap width.
8. The method for preparing a TPE-PP composite material for a folding joint of a pet stroller as described in claim 3, characterized in that, The online irradiation crosslinking device described in S3 has the following parameter settings: setting the electron energy to 5MeV and the dose to 10kGy.
9. The application of the TPE-PP composite material according to any one of claims 1-2 for the folding joint of a pet stroller, characterized in that, The granules of the composite material are processed into folding joint components through injection molding or compression molding, which are used in pet strollers where joint structures with both high rigidity and high fatigue resistance are required.
Citation Information
Patent Citations
EPDM / PP / TPE (Ethylene Propylene Diene Monomer / Polypropylene / Thermoplastic Elastomer) ternary blended closed-pore foaming material and preparation method thereof
CN103289213A
High-toughness long-glass-fiber reinforced polypropylene composite material and method for preparing same
CN103044764A
Fatigue-resistant glass fiber reinforced polypropylene composite material and preparation method thereof
CN114149636A